Comparative Analysis of PID Tuning Techniques for Blood Glucose Level of Diabetic Patient - et. al., Vandana Dubey, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The robustness and ease of execution has attention the use of Proportional, Integral and Derivative (PID) controllers in the field of biomedical engineering. One of the applications of PID controllers in field of Biomedical Engineering is to control the Blood Glucose Level of Diabetic Patient. PID works on the principle of closed loop system mechanism. The closed loop IDS (Insulin Delivery System) consist of 3 components: A glucose sensor, a control system for controlling insulin infusion and insulin pump. Several tuning methods are present for tuning of PID controllers; each one of it has its advantages and disadvantages. This paper deals the process for obtaining the controller technique of IDC using diverse tuning techniques and performance comparison of PID controller based on Process Reaction Curve tuning process and PID controller tuned with Ziegler-Nichols (Z-N), Integral of Time multiplied by Absolute Errors (ITAE), Approximate constrained Integral Gain Optimization (AMIGO) and Chien-Hrones-Reswick (CHR). The response shows that CHR-PID gives the flexibility of regulate for given desired performance in assessment to other tuning methods.